Innovative Approaches to Physics Education in Merdeka Curriculum: The Impact of STEM-Integrated Project-Based Learning on 21st Century Skills - Tantri, Risma; Udyaningsih, Putrie Syifa; Kuswanto, Heru (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
STEM-integrated project based learning (STEM-PjBL) is an ideal learning model recommended in the Merdeka Curriculum to achieve 21st century education goals, because it involves the principles of critical thinking, communication, collaboration, creativity, character, citizenship, and computational thinking skills. This study aims to explore the development of international and national research publications on the STEM-PjBL indexed by Scopus in the 2020-2024 period using a systematic literature review (SLR) assisted by the VOSViewer program, and to examine its impact on the achievement of 21st century skills. The analysis included 68 articles selected using the Prisma technique. This study proposes the following findings: (1) the implication that is often used is the type of quantitative research with quasi-experimental methods, the research subjects are students or students at the senior high school (SMA) level with a small scale sample size of less than 50 respondents, (2) research is widely used to analyze the achievement of creativity skills but no one has studied the impact of STEM-PjBL on citizenship skills. However, the PjBL-STEM model is proven effective for improving of 21st century skills so that it is suitable for the Merdeka Curriculum outcomes. Future research is expected to use additional bibliographic sources such as Web of Science and Google Scholar.